Marginal abatement cost curves for REDD+ in Kalimantan, Indonesia and the potential role of cost-saving plantations. (9th July 2018) - Lu, Heli; Liu, Guifang; Okuda, Toshinori; Zhang, Chuanrong
Abstract: Tackling climate action through REDD+ implementation is a viable option to climate action planning. This study aims to develop a marginal abatement cost (MAC) based process that enables decision-makers to estimate economic cost of emissions abatement and understand the role of cost-saving plantations in climate change planning practices. Our research in Kalimantan, Indonesia shows that cost-saving plantations can contribute to 0.05 million ton CO2 sequestration in research area. Further analysis suggests that cost-effective plantations account for 86% of total carbon emissions. The application of MAC curves for REDD+ in our study provides insights to include the optimization of land utilization in support of leveraging financial resources for the implementation of REDD+ strategies.